Lemma Time!

r = 1 19 ( 1 ) r 1 r ( 20 r ) \large \sum_{r=1}^{19} \frac{ (-1)^{r-1} r }{ {20\choose r} }

If the summation above equals to m n \frac mn for coprime positive integers m m and n n , find the value of m + n m+n .


The answer is 21.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Shubham Garg
Jul 19, 2015

S = i = 1 19 ( 1 ) r 1 × r ( 20 r ) S=\sum_{i=1}^{19} \frac{(-1)^{r-1} \times r}{20 \choose r}

Replacing r r by n r n-r and adding we get

S = 20 i = 1 9 ( 1 ) r 1 ( 20 r ) 10 ( 20 10 ) S=20\sum_{i=1}^{9} \frac{(-1)^{r-1}}{20 \choose r}-\frac{10}{20 \choose 10}

Now

1 ( n r ) = n + 1 n + 2 ( 1 ( n + 1 r + 1 ) + 1 ( n + 1 r ) ) \frac{1}{n \choose r} = \frac{n+1}{n+2}(\frac{1}{{n+1} \choose {r+1}}+\frac{1}{{n+1} \choose r})

Splitting each term we get

S = 20 × 21 22 ( 1 ( 21 1 ) + 1 ( 21 2 ) 1 ( 21 2 ) 1 ( 21 3 ) . . . . . . . . . + 1 ( 21 10 ) ) 10 ( 20 10 ) S=20 \times \frac{21}{22} (\frac{1}{21 \choose 1}+\frac{1}{21 \choose 2}-\frac{1}{21 \choose 2}-\frac{1}{21 \choose 3}.........+\frac{1}{21 \choose 10})-\frac{10}{20 \choose 10}

Consecutive terms will get cancelled

S = 20 × 21 22 ( 1 ( 21 1 ) + 1 ( 21 10 ) ) 20 × 21 22 × 1 ( 21 10 ) S=20 \times \frac{21}{22}(\frac{1}{21 \choose 1}+\frac{1}{21 \choose 10})-20 \times \frac{21}{22} \times \frac{1}{21 \choose 10}

Therefore

S = 10 11 S=\boxed{\frac{10}{11}}

Maggie Miller
Jul 20, 2015

For any positive even integer n n ,

r = 1 n 1 ( 1 ) r 1 r ( n r ) = r = 1 n 2 1 ( 1 ) r 1 n ( n r ) + ( 1 ) n 2 1 n 2 ( n n 2 ) = n 2 r = 1 n 1 ( 1 ) r ( n r ) \displaystyle\sum_{r=1}^{n-1}\frac{(-1)^{r-1}r}{{n \choose r}}=\sum_{r=1}^{\frac{n}{2}-1}\frac{(-1)^{r-1}n}{{n \choose r}}+\frac{(-1)^{\frac{n}{2}-1}\frac{n}{2}}{{n \choose \frac{n}{2}}}=-\frac{n}{2}\sum_{r=1}^{n-1}\frac{(-1)^{r}}{{n \choose r}}

= n 2 r = 0 n ( 1 ) r ( n r ) + n = n 2 ( 1 + ( 1 ) n ) ( n + 1 n + 2 ) + n =\displaystyle-\frac{n}{2}\sum_{r=0}^{n}\frac{(-1)^{r}}{{n \choose r}}+n=-\frac{n}{2}(1+(-1)^{n})\left(\frac{n+1}{n+2}\right)+n

= n ( n + 1 ) + ( n + 2 ) n n + 2 = n n + 2 . =\displaystyle\frac{-n(n+1)+(n+2)n}{n+2}=\frac{n}{n+2}.

Plugging in n = 20 n=20 , we find r = 1 19 ( 1 ) r 1 r ( 20 r ) = 20 22 = 10 11 , \displaystyle\sum_{r=1}^{19}\frac{(-1)^{r-1}r}{{20 \choose r}}=\frac{20}{22}=\frac{10}{11}, so the answer is 21 \boxed{21} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...